EXPERIMENTAL EVALUATION OF AIR-CONDITIONING SYSTEM - Erinle, Tunji John; Akinola, Adebisi Olayinka; Adesusi, Olanrewaju Moses; Agbamu, Idonorewrene Amudo (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2021)
This study focused on the experimental evaluation of an air-conditioning system of its coefficient of performance. The performance of any vapor compression system is evaluated by the operational coefficient of performance (COP). The aim was to evaluate the effect of parameters that affect the COP of a refrigeration system. Measurements of important operational parameters such as the evaporator and condenser temperatures were studied and measured from the system. Other relevant parameters such as the humidity of both the supply air and that of the space to be conditioned were also studied and measured. Experimental data were generated for 30 days to determine the performance of the air-conditioning system. Performance evaluation of the system was determined in terms of refrigerating capacity and COP. In this present study, the load was estimated, refrigerating effect, work input, and COP was estimated. The estimated results from the experimentation showed that the operational COP of the air-conditioning system range from 3.41 0.02 to 4.98 0.02. Efficiency requirement in Energy Efficiency Ratio (EER) for the air- conditioning system was estimated as 9.2. The coefficient of determination, R2 value also showed that the variables being compared have a strong correlation.